Implikasi Hukum Airdrop Kripto pada Aplikasi Telegram Sebagai Bentuk Promosi Aset Kripto - Imam Gunawan; Faridh Fikri (Universitas Proklamasi 45, 2025)
Telegram is a fast messaging platform and has become the main media for promoting crypto assets. Telegram's functionality establishes its position in innovation in the field of cryptocurrency, such as digital wallets and Peer to Peer markets. The implication is that Telegram, as a social media platform, has penetrated the cryptocurrency sector, one of which is the implementation of crypto airdrops. The purpose of this study is to provide a deeper understanding of the legal implications of crypto airdrops on the Telegram application as a form of crypto asset promotion, including the challenges and opportunities that exist in the context of Indonesian law. The method used in this study is normative legal research with a legislative approach and a conceptual approach. The results of this study are that crypto airdrops are a promotional or marketing strategy by crypto companies for new cryptocurrencies that will be issued. Crypto airdrops are classified into five parts, namely standard airdrops, bounty airdrops, holder airdrops, exclusive airdrops, and lottery airdrops. There are no regulations yet that determine how the crypto airdrop mechanism works in Indonesia. Therefore, the legal implications that occur in this discussion are the problem of Telegram as a social media expanding into the transaction service sector (crypto assets), the determination of new cryptocurrencies, and the problem of tax payments for airdrop hunters by reviewing several regulations in Indonesia, such as the Law, Bappebti Regulations, Ministerial Regulations, OJK Regulations, and other regulations.